A calculus problem by Rocco Dalto

Calculus Level pending

d x d t = y + x ( 1 x 2 y 2 ) d y d t = x + y ( 1 x 2 y 2 ) \frac{dx}{dt} = - y + x (1 - x^2 - y^2) \\ \frac{dy}{dt} = x + y (1 - x^2 - y^2)

The nonlinear system above has the solution x = x ( t ) x = x(t) , y = y ( t ) y = y(t) , where x ( t = 0 ) = y ( t = 0 ) = 1 2 . x(t = 0) = y(t = 0) = \dfrac{1}{2}.

If 0 ln ( 3 ) x ( t ) 2 + y ( t ) 2 d t \displaystyle \int_{0}^{\ln(\sqrt{3})} \sqrt{x(t)^2 +y(t)^2} \: dt can be expressed as
ln ( α + β α + λ ) \ln \left(\frac{\alpha + \sqrt{\beta}}{\sqrt{\alpha} + \lambda}\right) , where α \alpha , β \beta , and λ \lambda are coprime positive integers.

Find: α + β + λ \alpha + \beta + \lambda .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 4, 2016

d x d t = y + x ( 1 x 2 y 2 ) \: \dfrac{dx}{dt} = - y + x (1 - x^2 - y^2) d y d t = x + y ( 1 x 2 y 2 ) \: \dfrac{dy}{dt} = x + y (1 - x^2 - y^2)

Converting to polar coordinates, let x = r c o s θ , y = r s i n θ x = r cos\theta, y = r sin\theta ( 1 ) : x 2 + y 2 = r 2 , ( 2 ) : θ = arctan ( y x ) (1): \: x^2 + y^2 = r^2, (2): \: \theta = \arctan(\dfrac{y}{x})

Taking the derivatives with respect to t t of ( 1 ) (1) and ( 2 ) (2) we obtain:

r d r d t = x d x d t + y d y d t r \dfrac{dr}{dt} = x \dfrac{dx}{dt} + y \dfrac{dy}{dt}

r 2 d θ d t = x d y d t y d x d t r^2 \dfrac{d\theta}{dt} = x \dfrac{dy}{dt} - y \dfrac{dx}{dt}

x ( d x d t = y + x ( 1 x 2 y 2 ) ) x * (\dfrac{dx}{dt} = - y + x (1 - x^2 - y^2) ) y ( d y d t = x + y ( 1 x 2 y 2 ) ) y * (\dfrac{dy}{dt} = x + y (1 - x^2 - y^2) )

Adding the above equations we obtain: r d r d t = r 2 ( 1 r 2 ) d r d t = r ( 1 r 2 ) r \dfrac{dr}{dt} = r^2 (1 - r^2) \implies \dfrac{dr}{dt} = r (1 - r^2)

and, y ( d x d t = y + x ( 1 x 2 y 2 ) ) -y * (\dfrac{dx}{dt} = - y + x (1 - x^2 - y^2) ) x ( d y d t = x + y ( 1 x 2 y 2 ) ) x * (\dfrac{dy}{dt} = x + y (1 - x^2 - y^2) )

Adding the above equations we obtain:

r 2 d θ d t = r 2 d θ d t = 1 r^2 \dfrac{d\theta}{dt} = r^2 \implies \dfrac{d\theta}{dt} = 1

The system of differentials above has a single critical point at r = 0 r = 0 . Assuming r > 0 r > 0 , the system above reduces to:

d r d t = r ( 1 r 2 ) \dfrac{dr}{dt} = r (1 - r^2) d θ d t = 1 \dfrac{d\theta}{dt} = 1

d r r ( 1 r 2 ) = d t \implies \int \dfrac{dr}{r (1 - r^2)} = \int dt \implies

1 r + 1 2 ( 1 r ) 1 2 ( 1 + r ) d r = d t \int \dfrac{1}{r} + \dfrac{1}{2 (1 - r)} - \dfrac{1}{2 (1 + r)} \: dr = \int dt \implies

ln ( r 1 r 2 ) = t + K r 2 1 r 2 = C e 2 t \ln(\dfrac{r}{\sqrt{1 - r^2}}) = t + K \implies \dfrac{r^2}{1 - r^2} = C e^{2t} \implies

r 2 ( 1 + C e 2 t ) = C e 2 t r = C e 2 t 1 + C e 2 t r^2 (1 + C e^{2t}) = C e^{2t} \implies r = \sqrt{\dfrac{C e^{2t}}{1 + C e^{2t}}} r = 1 1 + C e 2 t \implies r = \dfrac{1}{\sqrt{1 + C e^{-2t}}} and, θ = t + t 0 \theta = t + t_{0}

x = r c o s ( t + t 0 ) , y = r s i n ( t + t 0 ) x = r cos(t + t_{0}), y = r sin(t + t_{0}) \implies

x ( t ) = c o s ( t + t 0 ) 1 + C e 2 t x(t) = \dfrac{cos(t + t_{0})}{\sqrt{1 + C e^{-2t}}} y ( t ) = s i n ( t + t 0 ) 1 + C e 2 t y(t) = \dfrac{sin(t + t_{0})}{\sqrt{1 + C e^{-2t}}}

Using initial conditions x ( t = 0 ) = y ( t = 0 ) = 1 2 x(t = 0) = y(t = 0) = \dfrac{1}{2} we obtain:

1 4 ( 1 + C ) = c o s 2 ( t 0 ) \dfrac{1}{4} (1 + C) = cos^2(t_{0})

1 4 ( 1 + C ) = s i n 2 ( t 0 ) \dfrac{1}{4} (1 + C) = sin^2(t_{0})

1 2 ( 1 + C ) = 1 C = 1 \implies \dfrac{1}{2} (1 + C) = 1 \implies C = 1 \implies

x ( t ) = c o s ( t + t 0 ) 1 + e 2 t x(t) = \dfrac{cos(t + t_{0})}{\sqrt{1 + e^{-2t}}} y ( t ) = s i n ( t + t 0 ) 1 + e 2 t y(t) = \dfrac{sin(t + t_{0})}{\sqrt{1 + e^{-2t}}}

Note: Using C = 1 t 0 = π 4 C = 1 \implies t_{0} = \dfrac{\pi}{4} here, but it's not needed for the integral below.

The integral I = 0 ln ( 3 ) x ( t ) 2 + y ( t ) 2 d t = I = \int_{0}^{\ln(\sqrt{3})} \sqrt{x(t)^2 + y(t)^2} \: dt =

0 ln ( 3 ) e t e 2 t + 1 d t \int_{0}^{\ln(\sqrt{3})} \dfrac{e^{t}}{\sqrt{e^{2t} + 1}} \: dt

Let e t = t a n θ d t = s e c 2 ( θ ) t a n θ d θ e^t = tan\theta \implies dt = \dfrac{sec^2(\theta)}{tan\theta} \: d\theta \implies

I = 0 ln ( 3 ) e t e 2 t + 1 d t = π 4 π 3 s e c ( θ ) d θ = I = \int_{0}^{\ln(\sqrt{3})} \dfrac{e^{t}}{\sqrt{e^{2t} + 1}} \: dt = \int_{\dfrac{\pi}{4}}^{\dfrac{\pi}{3}} sec(\theta) \: d\theta = ln ( s e c ( θ ) + t a n ( θ ) ) π 4 π 3 = \ln(sec(\theta) + tan(\theta))|_{\dfrac{\pi}{4}}^{\dfrac{\pi}{3}} =

ln ( 2 + 3 2 + 1 ) = ln ( α + β α + λ ) \ln(\dfrac{2 + \sqrt{3}}{\sqrt{2} + 1}) = \ln(\dfrac{\alpha + \sqrt{\beta}}{\sqrt{\alpha} + \lambda})

α + β + λ = 6 \implies \alpha + \beta + \lambda = \fbox{6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...